THE IMPACT OF THE FOREIGN DIRECT INVESTMENT ON ROMANIA’S ECONOMY - MIHAELA IONECI; GEORGIANA MÎNDRECI (Annals of the University of Petrosani: Economics)
Foreign direct investment can be regarded as a factor out of the crisisof the Romanian economy. The relationship between the foreign direct investment and the grossdomestic product is beneficial for the economy to the extent to which investment is directedtowards innovation and new technologies. The virtuous circle diversity - change - technologyneeds investment to take effect. Microeconomic level investment completes the strategies andthe investment decisions at macroeconomic level.